2013
DOI: 10.3109/08039488.2013.780260
|View full text |Cite
|
Sign up to set email alerts
|

Gaba transporterSLC6A11gene polymorphism associated with tardive dyskinesia

Abstract: These results suggest that GABA receptor signaling pathway was associated with the increased susceptibility to TD in Korean schizophrenic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…This study was approved by the Ethics Committee of the Korea University Hospital (06-2594), and all the participants provided written informed consent. Other characteristics of these subjects have been previously reported [ 11 - 15 ].…”
Section: Methodsmentioning
confidence: 89%
“…This study was approved by the Ethics Committee of the Korea University Hospital (06-2594), and all the participants provided written informed consent. Other characteristics of these subjects have been previously reported [ 11 - 15 ].…”
Section: Methodsmentioning
confidence: 89%
“…Allelic mutation represses SLC6A2 transcription [132] and confers to ADHD (attention-deficit hyperactivity disorder) [133]. Slc6a11 encodes GABA transporter 3, polymorphism of the gene increased the susceptibility to the tardive dyskinesia, an involuntary neurological movement disorder [134]. Slc6a15 functions as a brain transporter that facilitate the uptake of proline and leucine [135,136].…”
Section: Solute Carrier Genesmentioning
confidence: 99%
“…The role of GABA receptor genes GABRB2 and GABRG3 in TD has been investigated, but no significant associations were reported for the studied polymorphisms. However, gene-gene interactions between GABRB2 , GABRG3 , and SCL6A11 and susceptibility to TD highlighted the importance of the GABA receptor signaling pathway ( Son et al, 2014 ).…”
Section: Pharmacogenomic Studies Focusing On the Association Between Tardive Dyskinesia And Genes Involved In The Pharmacodynamicsmentioning
confidence: 99%
“…The protein encoded by SLC6A11 is a sodium-dependent transporter of GABA from synaptic cleft to surrounding glial cells leading to decreased GABA signaling. A case-control study, which included 180 patients with schizophrenia, 105 of whom experienced TD, identified an association between SLC6A11 rs4684742 and TD ( Son et al, 2014 ) (Summarized in Table 5 ). All of the studies are presented in this chaptercan be found in the Supplementary Table S2 .…”
Section: Pharmacogenomic Studies Focusing On the Association Between Tardive Dyskinesia And Genes Involved In The Pharmacodynamicsmentioning
confidence: 99%